The culture of learning science in a Sabah Islamic religious secondary school science classroom - Amnah Abdullah (2019)
The aim of this study was to explore in-depth i.e. to describe, to explain, to understand, and verstehen, the culture of learning science in the classroom of a religious secondary school. I used interpretive paradigm philosophy, with ethnography methodology. My methods used to obtain the data of informants in their natural setting were essentially fieldnotes, observations, and interviews. Supporting materials i.e. visual materials, documents were also used. The themes discovered in this study were priority, value-laden, and inequities. I found that culture did influenced the learning of science, but the achievement of students was much related to inequities and not culture. On the contrary, the components of culture in this study i.e. priority and value-laden enhanced and motivated the students to be psychologically stable in their duties as a student fulfilling three of the four national philosophy of education components i.e. spiritually, emotionally, and physically. However, inequities had made fulfilling the component intellectually unachievable. I discovered that my informants lacked the cognitive apprenticeship needed to be a future member of the scientific enterprise. In Sabahan context, the relationship between Reading Qur'an, Rote Learning, and Respect Elders was uncovered. This relationship was within the Sociocultural Theory incorporating the two levels i.e. social level and individual level. I presented through conference the proposed expanded theoretical framework leading to the value of putting the lens on the subculture learner in order to understand the end user of the curriculum (i.e. the students). The practice of classroom ethnography in the understanding of minority groups in Sabah context was also argued in my discourse. This study fulfilled the decentralization of the reformed education system where states, districts could identify needs and find customized solutions to their customized needs related to their environment and culture. This research is expected to provide a sharing of information that could be used by the district, state, and MOE if it was relevant to be implemented. Finally, the implementation and further study could be conducted on students in different classes. Future studies could also be conducted using an intervention design of an integrated model cultural knowledge-science knowledge to test the effectiveness of teaching students using an integrated curriculum in the goal of improving the achievement rate of secondary students in minority religious schools.